α-Synuclein-induced lysosomal dysfunction occurs through disruptions in protein trafficking in human midbrain synucleinopathy models - Mazzulli, Joseph R.; Zunke, Friederike; Isacson, Ole; Studer, Lorenz; Krainc, Dimitri (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Parkinson's disease (PD) is an age-related neurodegenerative disorder characterized by the accumulation of protein aggregates comprised of α-synuclein (α-syn). A major barrier in treatment discovery for PD is the lack of identifiable therapeutic pathways capable of reducing aggregates in human neuronal model systems. Mutations in key components of protein trafficking and cellular degradation machinery represent important risk factors for PD; however, their precise role in disease progression and interaction with α-syn remains unclear. Here, we find that α-syn accumulation reduced lysosomal degradation capacity in human midbrain dopamine models of synucleinopathies through disrupting hydrolase trafficking. Accumulation of α-syn at the cell body resulted in aberrant association with cis-Golgi-tethering factor GM130 and disrupted the endoplasmic reticulum-Golgi localization of rab1a, a key mediator of vesicular transport. Overexpression of rab1a restored Golgi structure, improved hydrolase trafficking and activity, and reduced pathological α-syn in patient neurons. Our work suggests that enhancement of lysosomal hydrolase trafficking may prove beneficial in synucleinopathies and indicates that human midbrain disease models may be useful for identifying critical therapeutic pathways in PD and related disorders.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Induced pluripotent stem cells; Long-term midbrain culture; Parkinson's disease; Protein trafficking; Synucleinopathies